Geotechnical Frontiers 2025 - Foundations, Retaining Structures, and Geosynthetics - Beauregard Melissa S; Budge Aaron S (American Society of Civil Engineers (ASCE), 2025)
Selected papers from Geotechnical Frontiers 2025, held in Louisville, Kentucky, March 2-5, 2025. Sponsored by the Geosynthetic Materials Association, Advanced Textiles Association, and the Geo-Institute of ASCE. This Geotechnical Special Publication contains 54 peer-reviewed papers on foundations, retaining structures, and geosynthetics. Topics include: deep foundations; earth retaining structures; and geosynthetics. GSP 364 will be of interest to geotechnical engineers, researchers, contractors, and other geoprofessionals working with various foundation types.